Investigating gender differences in the factor structure of the Gudjonsson Compliance Scale - Drake, Kim E. (Legal and criminological psychology, 2017)
Purpose. The Gudjonsson Compliance Scale (GCS) remains, in terms of its psychometrics, an under-researched instrument, in which gender differences in particular have been insufficiently examined. The aim of this research was to therefore investigate the effect of gender on the factor structure of the GCS. Method. The GCS was administered to 441 females and 250 males. The data were factor-analysed, with 1-, 2-, 3-, and 4-factor solutions tested and compared. Procrustean rotation was applied to the male factor loading matrix to investigate structural equivalence across gender. Results. Although a 3-factor solution was the best fit to the male GCS data, a 4-factor solution was the most acceptable fit to the female data. Whilst each of the factors had a high degree of determinacy, the identity coefficients indicated that these factors differ non-trivially across gender. Conclusion. The GCS may measure different aspects of compliance across males and females, which may explain the gender differences in compliance found within the literature to date. The work also allows insight into why males and females may end up complying with police requests, which might ultimately help to inform strategies, implemented by police, to manage vulnerable general population suspects and witnesses. There is a need now to further investigate the structure of compliance across ethnic groups and/or countries where the GCS is administered.